1994
DOI: 10.1111/j.1526-4610.1994.hed3408s17.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Headache Syndromes in the Community

Abstract: The present study investigated the association between psychopathology and headache in a prospective longitudinal epidemiologic study of a cohort of 19-and 20-year-olds in Zurich, Switzerland. Prevalence rates of psychopathology by headache subtype were examined both cross-sectionally and longitudinally. Psychiatric disorders were evaluated using a direct interview administered by experienced clinicians. Personality was assessed using the Freiburg Personality Inventory and the Symptom Checklist 90. In general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
54
3
9

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 30 publications
(30 reference statements)
10
54
3
9
Order By: Relevance
“…In epidemiologic studies an association was found between migraine and panic attacks [11] and both depression and anxiety disorders [12][13][14][15][16][17]. This was confirmed by prospective studies [18][19][20]. Some caution in interpreting our data is requested by the fact that the work was performed on a selected sample of patients seeking treatment in a specialty center.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In epidemiologic studies an association was found between migraine and panic attacks [11] and both depression and anxiety disorders [12][13][14][15][16][17]. This was confirmed by prospective studies [18][19][20]. Some caution in interpreting our data is requested by the fact that the work was performed on a selected sample of patients seeking treatment in a specialty center.…”
Section: Discussionsupporting
confidence: 48%
“…This issue also relates to the problem whether an association exists between personality changes and migraine. While clinical investigations using the Minnesota multipolar personality inventory (MMPI) in migraine patients led to controversial results [6][7][8][9][10][11][12][13], epidemiologic and prospective studies [14][15][16][17][18][19][20][21][22][23] have confirmed this association. On the other hand, since behavioral and somatic symptoms are observed in patients with anxiety, mood and somatoform disorders [24], the assessment of their prevalence in a migraine patient population may be of help in evaluating the psychogenic component in these patients.…”
Section: Introductionmentioning
confidence: 95%
“…[24][25][26][27] Fewer studies have been published assessing tension-type headaches and psychiatric comorbidity. Nonetheless, the evidence is fairly consistent that tension headache patients are more likely than healthy controls to suffer from psychiatric disorders, especially anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Highly HA individuals are described as extremely careful, passive, fearful, insecure and prone to react with a high rate of anxiety and depression to stressful events, while high P levels express the tendency to maintain unrewarded behaviours and correlate with rigidity and obsessiveness [1]. Low levels of SDir are an important predictor of categorical diagnosis of DSM Axis I disorders which are frequently associated with migraine [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…As mood and anxiety disorders are a frequent finding in headache patients [5][6][7][8], the question arises as the extent to which the differences in TCI dimensions observed in migraine patients depend on the headache pathology or on the presence of depression. Both pathologies are indeed characterised by the involvement of the serotoninergic system.…”
Section: Introductionmentioning
confidence: 99%